Artificial intelligence systems and the right to good administration - Wróbel, Izabela Małgorzata (Review of European and Comparative Law, 2022)
The use of AI in public administration is becoming a reality, although it is still a long way from large-scale undertakings . The right to good administration, well-established in EU legal order, is equally real, however, it must be borne in mind that this right has so far been defined only in relation to traditional administration . Therefore, the purpose of the paper is to examine whether the use of AI in public administration would allow individuals to fully exercise their right to good administration. To achieve this purpose, it is reconstructed, on the basis of EU law provisions in force and the case-law of the CJEU, the meaning and scope of the right to good administration, and analysed, taking into account a definition of AI systems and planned legislative changes, whether and to what extent the reconstructed understanding of this right enables the use of AI systems in public administration. In the course of research the hypothesis that the right to good administration does not preclude the use of AI systems in public administration is verified . As the conducted analysis shows, the right to good administration as interpreted in traditional administration enables the use of AI systems in public administration, provided that the appropriate quality of these systems and the level of knowledge and skills of the parties and authorities are ensured.